PENGEMBANGAN VIDEO ANIMASI SEBAGAI MEDIA EDUKASI ADAB BERSOSIAL MEDIA PADA MATA PELAJARAN PENDIDIKAN PANCASILA PADA KELAS IV SDN 172 INPRES LIMAPOCCOE - Andi Tenri Ulang; Ahmad Syawaluddin; Bhakti Prima Findiga Hermuttaqien (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to produce animated videos as educational media on social media etiquette in the Pancasila education subject for fourth-grade students at SDN 172 Inpres Limapoccoe. The research method used in this study is Research and Development (R&D). The development model used by the researcher was the ADDIE model. The population in this study consisted of 27 fourth-grade students at SDN 172 Inpres Limapoccoe. The results of this study showed that the validation results obtained by subject matter experts were 75% (good), while the validation results obtained by media experts were also 75% (good). After conducting validation with experts, a teacher response test was carried out with a percentage of 82% (very good), a student response test with a percentage of 76% - 93% (very good), and a small group trial was conducted with 6 students. Thus, the research on the development of animated videos as a medium for educating social media etiquette is categorized as very good.